The Level of Emotional Intelligence among Principals of Basic Education Schools in Al dakhiliyah Governorate in the Sultanate of Oman from the Teacher's Point of View. (Journal Of Educational and Psychological Researches, 2023)
AbstractThis study aims to identify the level of emotional intelligence among principals of basic education schools in Al-Dakhiliya Governorate. The descriptive approach was used. A questionnaire of two parts was utilized; its second part included (27) items divided into five dimensions related to emotional intelligence. The study sample consisted of (337) teachers representing 52% of the study sample were randomly selected. The study result showed that level of the emotional intelligence is high and the motivation dimension is the highest. There were no statistical differences at the level (α≤ 0.05) due to the impact of (the social type, the educational qualification, and the years of experience) in all the emotional intelligence dimensions. In the light of these results, there are some recommendations such as providing training workshops for the schools’ principals in relation to management and how to affect the workers positively.